2015
DOI: 10.1111/eos.12231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an oxygen‐inhibited layer on enamel bonding of dental adhesive systems: surface free‐energy perspectives

Abstract: The influence of an oxygen-inhibited layer (OIL) on the shear bond strength (SBS) to enamel and surface free-energy (SFE) of adhesive systems was investigated. The adhesive systems tested were Scotchbond Multipurpose (SM), Clearfil SE Bond (CS), and Scotchbond Universal (SU). Resin composite was bonded to bovine enamel surfaces to determine the SBS, with and without an OIL, of adhesives. The SFE of cured adhesives with and without an OIL were determined by measuring the contact angles of three test liquids. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
5
0
3
Order By: Relevance
“…The γnormalSp measurement involves the polar interaction and reflects the degree of polarization . The γnormalSh measurement is also related to the hydroxyl groups and reflects hydrophilic interaction . Therefore, phosphoric acid pre‐etching of enamel demineralizes the smear layer and superficial enamel, and increases the number of hydroxyl sites and hydrophilicity, leading to increased γnormalSp and γnormalSh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The γnormalSp measurement involves the polar interaction and reflects the degree of polarization . The γnormalSh measurement is also related to the hydroxyl groups and reflects hydrophilic interaction . Therefore, phosphoric acid pre‐etching of enamel demineralizes the smear layer and superficial enamel, and increases the number of hydroxyl sites and hydrophilicity, leading to increased γnormalSp and γnormalSh.…”
Section: Discussionmentioning
confidence: 99%
“…The surface free‐energy value of a solid is considered to be a useful indicator of the wettability of the surface in the Kitazaki–Hata extension of the Young–Dupré theory . Surface free‐energy values are composed of the dispersion force (γnormalSd), the polarity force (γnormalSp) and the hydrogen‐bonding force (γnormalSh), in which γnormalSd is one aspect of the van der Waals forces, γnormalSp represents the degree of polarization of the surface, and γnormalSh indicates the hydrophilicity of the surface . Therefore, the surface free‐energy characteristics of enamel might provide insights into the influence of duration of phosphoric acid pre‐etching on bond durability of universal adhesives.…”
mentioning
confidence: 99%
“…Our results are compatible with other reports on the same and various other composites 18,28) . The SFE analysis is used to estimate the chemical state of a material surface 15,[31][32][33][34][35][36][37][38][39][40] . We reported that the SFE is strongly correlated to the microstructure of the CAD/CAM composite, affecting its adhesion to the resin cement in our previous report 15) .…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, contact angle measurements on hard surfaces provide information about surface-free energy in relation to bonding characteristics of the solid materials [14,15]. Surface free-energy of a solid is defined as an indicator of surface wettability and comprises dispersion forces, polarity forces, and hydrogen-bonding forces [16,17]. While dispersion forces are one aspect of van der Waals forces, polarity forces represent electric/metallic interactions and dipolar interactions, and hydrogen-bonding forces indicate surface hydrophilicity [16,17].…”
Section: Palavras-chavementioning
confidence: 99%